Design and Synthesis of New Cyclic Imides Derived from 4-[ N-(2-Amino Thiazole-4-Yl]) Sulfamethexazole with Evaluation of their Antimicrobial Activity - Sadiq, Zainab Majid; Al-Azzawi, Ahlam Marouf (Iraqi Journal of Science, 2025)
This study introduces a series of novel cyclic imides, which incorporate two biologically significant components - the thiazole ring and sulfonamide. These target imides were developed using a method of multistep synthesis. The chosen starting material was the compound sulfamethoxazole, which is known to contain a biologically active sulfonamide. In the first step, sulfamethoxazole was reacted with chloroacetyl chloride, yielding compound [1] (4-N-(2-chloro acetamido) sulfamethoxazole) followed by reaction of compound [1] with thiourea provided a cure [2]. (4-(sulfamethoxazole-].4-y1)-2-aminothiazole) was obtained. Compound [2] played a major role and was successfully included in the third stage of the reaction with various cyclic anhydrides including succinic, phthalic, maleic, glutaric anhydride etc. This reaction led to the synthesis of the corresponding aromatic acids [3-6]. The fourth step of amic acid dehydration using the fusion method [3-6] successfully achieved the goal, resulting in the synthesis of new imides [7-10]. Additionally, the study involved the synthesis of a new cyclic imide [11] (sulfamethoxazole thiazole tetrachloro phthalimide) through a one-step process. This process involved the fusion of compound [2] and tetrachlorophthalic anhydride. Finally, the newly synthesized imides were screened for their antimicrobial activities, and the obtained results were promising.